Stream channel network analysis applied to colony-wide feeding structures in a Permian bryozoan from Greenland. Issue 2 (8th April 2011) - Key, Marcus M.; Jackson, Patrick N. Wyse; Vitiello, Louis J.
Abstract : Colony-wide feeding currents are a common feature of many bryozoan colonies. These feeding currents are centered on excurrent macular chimneys that expel previously filtered water away from the colony surface. In some bryozoans these macular chimneys consist of a branching channel network that converges at a point in the center of the chimney. The bifurcating channels of the maculae are analogous to a stream channel network in a closed basin with centripetal drainage. The classical methods of stream channel network analysis from geomorphology are here used to quantitatively analyze the number and length of macular channels in bryozoans. This approach is applied to a giant branch of the trepostome bryozoan Tabulipora from the Early Permian Kim Fjelde Formation in North Greenland. Its large size allowed 18 serial tangential peels to be made through the 8-mm-thick exozone. The peels intersected two stellate maculae as defined by contiguous exilapores. The lengths of 1460 channels radiating from the maculae were measured and their Horton-Strahler stream order and Shreve magnitude scored. We hypothesize that if fossil bryozoan maculae function as excurrent water chimneys, then they should conform to Horton's laws of stream networks and behave like closed basins with centripetal drainage. Results indicate that the stellate maculae in this bryozoan behaved liked stream channel networks exhibiting landscape maturation and stream capture. They conformed to the Law of Stream Number. They have a Bifurcation Ratio that falls within the range of natural stream channel networks. They showed a pattern opposite that expected by the Law of Stream Lengths in response to behavior characteristic of a centripetal drainage pattern in a closed basin. Thus, the stellate maculae in this bryozoan probably functioned as excurrent water chimneys with the radiating channels serving to efficiently collect the previously filtered water, conducting it to the central chimney for expulsion away from the colony surface.